L'actualisation des dommages-intérêts en matière de préjudice corporel - Gardner, Daniel (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
Since 1978 the evaluation of pecuniary loss resulting from personal injury genuinely derives from the restitutio in integrum principle. In this context the operation of discounting the portion of the lump sum indemnity representing the victim's future losses takes on particular importance. The method used by the Supreme Court has been considerably improved: the refusal to consider interest rates and inflation rates separately, the recognition of a productivity factor for losses representing future salaries, etc. Four provinces have decided to legislate on one or more discount rates to make up for the absence or inadequacy of evidence at this level. Despite legislative and courtroom activity, much remains to be done in improving both the present legal system and its replacement by a regime better adapted to the specific problems inherent in evaluating pecuniary losses.